A Helmet Use Reduces Injury in Mild Head Trauma with Multiple Injuries: A Case Report - Kailani, Dzaka Ogan Amirudin Lutfi; Hidayati, Titiek; Briliian Wahyudi, Rizqy (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2025)
Introduction : Patients with head injuries have a high risk of organ trauma. Organ trauma can occur in conjunction with head injuries, especially in cases of accidents involving violent impact. The energy of the impact usually does not affect only one area of the body. The head may be lightly impacted, but other parts of the body may also be injured. Not all parts of the body receive the same severity of impact. The head may suffer minor injuries while other parts of the body may suffer more severe injuries. Case precentation : A 22-year-old man came to the emergency department of Yogyakarta City Hospital delivered by an ambulance with complaints of lower abdominal pain, the pain felt widespread, the patient complained of not being able to eat and drink, nausea and vomiting, left leg pain when lifted. Physical examination revealed vulnus excoriation. The diagnosis of mild head injury accompanied by multiple trauma can be established by history taking, physical examination, neurological examination, and supporting examinations such as laboratory, X-ray, and abdominal ultrasonography. Discussion : Non-helmeted riders experience more severe head and facial injuries than helmeted riders. Riders who did not wear helmets had poorer mental status than those who did, and their mean GCS scores were usually lower than those who wore helmets. This suggests that there is a relationship between head protection, or helmets, and the severity of motorcyclists' injuries, and that when motorcyclists do not wear helmets, injuries and the risk of injury are greater. Conclusion : The patient suffered a mild head injury with multiple organ trauma after physical and supporting examinations. The patient's head injury can be minimized because the patient was still wearing a helmet at the time of the accident.